Ipsilateral neck radiotherapy in N2b well‐lateralized tonsil cancer – Approach with caution. Issue 9 (6th May 2019) - Maskell, David; Buckley, Hannah; Sission, Katherine; Roques, Tom; Geropantas, Konstantinos
Abstract: Background: Treatment of the uninvolved neck in well‐lateralized tonsillar squamous cell carcinoma is controversial. We became concerned after a number of contralateral neck recurrences (CNRs) in patients receiving ipsilateral radiotherapy (RT). Methods: This is a single center retrospective series including patients with well‐lateralized tonsillar cancer treated with ipsilateral neck RT between 2004 and 2011. Results: We identified 53 patients treated with ipsilateral neck RT during the study period. The rate of CNR was 7.5% (4 of 53). All four patients had p16‐positive, T1, N2b, M0 tumors. The subgroup of patients with N2b disease (28 of 53) had a CNR of 14.3%. We subsequently switched to treat patients with N2b with bilateral neck RT. We analyzed the outcomes of 23 patients with N2b treated with bilateral neck intensity‐modulated RT (IMRT) and observed no CNRs. Conclusions: We observed a higher than expected rate of CNR in the N2b population. Bilateral neck IMRT for these patients represents a safe alternative.